Properties of lithium niobate - Wong, K. K. (INSPEC/Institution of Electrical Engineers, 2002)
Annotation The use of lithium niobate in signal filtering in TV sets and video cassette recorders is well established and it is finding increased application in optoelectronic modulation devices in DWDM (dense wavelength division multiplexing) fiber optic systems. Much LiNbO3 research has taken place in recent years. This fully illustrated volume brings electronic engineers, materials scientists and physicists up-to-date by enlisting the expertise of active researchers and presenting their considered reviews in the modular form which characterizes the Datareviews series.
Keywords: Lithium niobate.; elektronické knihy; electronic books